2015
DOI: 10.29359/bjhpa.07.4.09
|View full text |Cite
|
Sign up to set email alerts
|

Imagery use in rehabilitation after the knee joint arthroscopy

Abstract: Background: The objective of the study was to assess the efficiency of visualization training based on motivating instructions of a general character in order to increase the knee joint mobility, reduce pain and increase the quadriceps muscle mass of the thigh in patients after the knee joint arthroscopy. Material/Methods: F10 outpatient clinic patients after arthroscopy of the knee joint (average age 35 yrs) were subject to research. Physiotherapeutic treatment comprised an improvement program to increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…MI and/or action observation have been established to improve motor learning and activate brain areas corresponding to motor planning and voluntary movement. 31 In the present scoping review, we found 15 studies 1630 applying these two techniques in rehabilitation, with six articles implementing action observation training, 1621 eight articles employing MI, 2228,30 and only one article studying combining MI with action observation in their protocol. 29 The benefits associated with using action observation in rehabilitation were related to an improvement in performing daily life activities.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…MI and/or action observation have been established to improve motor learning and activate brain areas corresponding to motor planning and voluntary movement. 31 In the present scoping review, we found 15 studies 1630 applying these two techniques in rehabilitation, with six articles implementing action observation training, 1621 eight articles employing MI, 2228,30 and only one article studying combining MI with action observation in their protocol. 29 The benefits associated with using action observation in rehabilitation were related to an improvement in performing daily life activities.…”
Section: Discussionmentioning
confidence: 88%
“…The majority of studies which employed MI interventions used functional tests, 22,[24][25][26][27][28][29][30] with MI training demonstrated to lead to improvements in several test scores (Table 3). Improvements in the ability to perform daily life activity, range of motion, 23,26,28 perception of pain, 24,27 muscle strength, 25,26,30 electromyography, 22 and neurobiology/physiological factors, 23,24 were observed. The visualization interventions 18,23 resulted in improvements in the ability to perform daily life activity, range of motion, neurobiology/physiological factors, and time to discharge.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The findings of Choi et al [ 20 ] indicated that both physical balance training with visual feedback and mental balance training with motor imagery were effective for healthy adults. For instance, mental training based on visualization may influence the athlete’s functional state; moreover, when reducing or increasing psychophysical stimulation, visualization-based mental training may affect one’s emotional states [ 21 ]. Some studies suggest that mental training could be used effectively to improve motor skills or task performance because of its lower energy consumption than physical training [ 22 ].…”
Section: Introductionmentioning
confidence: 99%